China's energy security strategy in Asia - Yang, Yi (2010)
China's shift to a net oil importer has generated much speculation about how China's growing dependence on foreign oil will affect its energy strategy. This discussion is framed by three sections. First part is to introduce the current energy profile to point out the main risks China's energy industry faced. Second, China's energy transportation security will be debated fkom economic, and political perspectives. Before doing so, this dissertation illustrates the major international oil and gas transportation models and compares the advantages and disadvantages of each model. In the third part, some major energy strategies implemented will be introduced to show whether they do work for China's energy security. This paper concludes that facing so many severe challenges, China can secure its energy security, both supply and transportation perspectives through multi-direction, and multi-level cooperation, from international, regional, to domestic level.